ANALYSIS OF PRODUCTIVITY AND BUSINESS FEASIBILITY GOMBANG FISHERY IN THEDISTRICT MESKOM VILLAGE BENGKALIS RIAU PROVINCE - Norman Suata Simamora; Isnaniah Isnaniah; Nofrizal Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis research will be conducted in July 2021 in Meskom Village, Bengkalis Regency, Riau Province. This study aims to determine productivity, calculate investment, calculate fixed and variable costs, and analyze the business feasibility of gombang fishing gear. The method used in this research is a survey method by making observations and observations directly into the field with structured interview techniques. The method used in this research is census taking. Samples were taken as much as 1 person from 30 fishermen who use gombang fishing gear in Meskom Village. During the research at Meskom Village, the productivity on November 3, 2020 was 15 kg and the CPU was 3.75 kg. The collection of gombang catches in Meskom Village is carried out in 1 day and one night for 4 hauling times, namely at two times the tide and two receding times that occur at night and during the day. The details of the feasibility calculation for the wave fishery business are as follows:Benefit Cost Ratio (BCR) is 1.9, which means B / C> 1, so the gombang fishery business is feasible to continue.The Financial Rate of Return (FRR) obtained from this gombang fishery business is 1%.The payback period of capital (PPC) is 1.3, which means that the time required for capital recovery is 1 year and 3 monthsKeywords: Produtivity; Feasibility; Gombang; in Meskom Village